Metafory wędrówki w Tanachu. Wizualizacja hebrajskiego rdzenia = Wandering metaphors in the Tanakh. A visualization of the Hebrew stem - Termińska, Kamilla (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The topos of human life as wandering, which is widely represented in the Tanakh, is referred to, among other things, by the stem "BR", the textual updates of which are discussed in the presented article. The visualized core generates numerous expressions directly or metaphorically related to wandering. Worth emphasizing is not only the individual but especially the communal nature of wandering.
Keywords: picture semantics; rdzeń "BR" i jego tekstowe aktualizacje; metafora wędrówki; metonimia wędrówki; the root "BR" and its textual updates; metaphor of wandering; metonym of wandering